Impact of Laser Energy on Features of Carbon Nanostructure Materials Prepared by A One-Step Pulsed Laser Ablation in Water - Addie, Ali; Khashaan, Khawla Salah; Saimon , Jehan; Hassan , Azhar (Iraqi Journal of Science, 2021)
Carbon nanoparticles (CNPs) formed by one-step laser ablation in deionized water were carefully studied. Scanning electron microscopy, atomic force microscopy, Raman spectroscopy, and UV–V spectroscopy were used to obtain morphological, chemical, and optical properties of CNPs. SEM outcomes established that the synthesized nanoparticles are semi-spherical with a wide particle size distribution. Raman investigation showed two typical and expected peaks ~ (1300 - 2700) cm−1, which are confirming to transverse and longitudinal modes of the carbon structure. The absorption spectra proved that the intensity of spectra increases as particle size and concentration increase.